Exploring The Importance Of English Proficiency: An Analysis Of The Intended And Enacted Curriculum Of The Pismp Tesl Programme At The Institute Of Teacher Education - Subramaniam, Nithiavani (Universiti Sains Malaysia, 2024)
The demand for highly proficient TESL teachers has become a national concern, driven by the widespread issue of poor English proficiency among current English language teachers in Malaysia. In response, in-service teachers who did not meet the required proficiency levels were enrolled in the Professional Up-skilling of English Language Teachers (Pro-ELT) programme. This situation raises questions about the effectiveness of pre-service training in addressing proficiency needs, leading to this study’s focus on the importance of English proficiency within the PISMP TESL programme offered at Institutes of Teacher Education in Malaysia. This qualitative case study aimed to analyse the extent to which English proficiency is prioritised in both the intended and enacted curriculum of the PISMP TESL programme. Content analysis of relevant curriculum documents was conducted to determine how proficiency is explicitly addressed in the intended curriculum. Additionally, semi-structured interviews with six teacher educators and eight student teachers were used to gather insights into the emphasis placed on proficiency in the enacted curriculum. Participants were selected from two Institutes of Teacher Education in Malaysia. The findings reveal that English proficiency is not given significant importance in either the intended or enacted curriculum of the PISMP TESL programme. This research concludes that there is a critical need for policymakers, administrators and teacher educators to re-evaluate and enhance the curriculum.